Kraków as a City of Creative Class – Adaptation of the Concept of R. Floryda - Kwaśny, Jakub; Mroczek, Arkadiusz (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The purpose of this article is to attempt to answer the question whether Cracow is a city that meets the criteria for "creative cities", attracting people who are recognized in R. Florida’s concept as an important factor in economic development. The authors, starting with the theoretical basis of the discussed issues, describe the present situation of the capital of Malopolska in comparison with the biggest Polish cities or their teams. It’s a simple comparative study in which Cracow is the main subject. This choice was not random, since the city intuitively seems to meet certain conditions to qualify it for recognition as the "Florida’s city".